Penerapan Naive Bayesian Classifier Dalam Penyeleksian Beasiswa PPA - Cici Alfiani Pradika Dita; Putri Chairunisyah; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In this study, the author uses the Naïve Bayes Classifier method to classify scholarship recipients at Budi Darma University. The use of the Naïve Bayes Classifier method was chosen to make decisions in order to determine whether students enrolled in the scholarship program were accepted or rejected. The classifier method is to classify text based on the highest probability that it is defined as a new document category. From the results of this research, the results show that the value of